Impact of Sales Growth, Corporate Risk, Profitability, and Liquidity on Tax Avoidance Strategies - Sari, Indah Rahma; Madjid, Suhirman (Taxation and Public Finance, 2025)
This study seeks to examine the impact of sales growth, company risk, profitability, and liquidity on tax avoidance. The research focuses on manufacturing firms within the pharmaceutical and healthcare sectors. Employing a quantitative research methodology, the study drew its sample from 10 firms selected through purposive sampling. Secondary data were gathered from the financial statements of these firms. The analysis was conducted using multiple linear regression techniques, incorporating descriptive statistical analysis, classical assumption tests, and hypothesis testing. The findings from the regression analysis indicate that both sales growth and profitability have a negative effect on tax avoidance. At the same time, company risk and liquidity do not significantly influence tax avoidance. This study contributes empirically to the understanding of how internal company factors, such as sales growth and profitability, affect tax avoidance strategies, specifically in the pharmaceutical and healthcare manufacturing sectors in Indonesia. Additionally, it serves as a practical reference for more ethical and effective tax planning. The managerial implications suggest that firms should carefully manage these factors to achieve a balance between optimizing tax liabilities and meeting their tax obligations.